Duty of the School Principal: meanings constructed in public schools - Abdian, Graziela Zambao [UNESP]; Andrade, Ederson Pereira [UNESP] (Univ Nove Julho, 2015)
This article aims to analyze the meanings constructed by the principal from public schools about their duties and management of their schools. To understand these meanings semi-structured interviews we conducted, with principals elected, gazetted and indicated, in two states of Brazil, in the State of Sao Paulo and in the State of Rio Grande do Sul. The results indicate that it isn't possible to establish fixed and generalized assertions about the relation between duty and form of provision of principals, because the daily interactions and processes of subject constitution prevent it to become effective. The way of provision of the position of Principal is only one element that comes across through the formation of meanings about his duty. The education policy and the rules established do not determine exclusively the school experiences, because the subjects do politics in the daily school life, meaning that in the school there is management policy.
Keywords: School principal; Duties of the school principal; Public school